2022
DOI: 10.1002/dys.1721
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal processing and transposed‐letter effects in dyslexic reading

Abstract: During parafoveal processing, skilled readers encode letter identity independently of letter position (Johnson et al., 2007). In the current experiment, we examined orthographic parafoveal processing in readers with dyslexia. Specifically, the eye movements of skilled readers and adult readers with dyslexia were recorded during a boundary paradigm experiment (Rayner, 1975). Parafoveal previews were either identical to the target word (e.g., nearly), a transposed‐letter preview (e.g., enarly), or a substituted‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…In fact, parafoveal recognition of embedded letters and words has been proven to be worse in dyslexic subjects than in normal controls [ 34 , 35 , 36 ]. Furthermore, reduced and delayed parafoveal preview benefits have been associated with dyslexia [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, parafoveal recognition of embedded letters and words has been proven to be worse in dyslexic subjects than in normal controls [ 34 , 35 , 36 ]. Furthermore, reduced and delayed parafoveal preview benefits have been associated with dyslexia [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that readers are able to process information about upcoming words in a sentence, that is, in the parafoveal field of vision, before their eyes move to fixate on them directly (reviews in Andrews & Veldre, 2019; Hyönä, 2011; Schotter et al, 2012; Vasilev & Angele, 2017). Eye movement studies have shown that skilled adult readers routinely process the orthography of upcoming words (Balota et al, 1985; Binder et al, 1999; Briihl & Inhoff, 1995; Inhoff, 1987, 1989a, 1989b, 1990; Inhoff & Tousman, 1990; Johnson & Dunne, 2012; Johnson et al, 2007; Kirkby et al, 2022; McConkie & Zola, 1979; Milledge et al, 2021; Milledge, Liversedge, & Blythe, 2022; Pagán et al, 2016; Rayner, 1975b; Rayner, McConkie, & Zola, 1980; Staroverova et al, 2023; Tiffin-Richards & Schroeder, 2015a; White et al, 2008; Williams et al, 2006), the phonology of upcoming words (Ashby & Rayner, 2004; Ashby et al, 2006; Chace et al, 2005; Henderson et al, 1995; Milledge, Liversedge, & Blythe, 2022; Pan et al, 2016; Pollatsek et al, 1992, 2000; Tiffin-Richards & Schroeder, 2015a; Vasilev et al, 2019), as well as the semantics of words visible in the parafovea (for discussions see Hohenstein & Kliegl, 2014; Rayner et al, 1986, 2014; Schotter et al, 2012, 2023; Veldre & Andrews, 2016; Yan et al, 2009). Although the extent of semantic processing in the parafovea is still debated, there is a consensus based on consistent replications that the integration of orthographic and phonological codes across fixations is an important aspect of skilled reading (Cutter et al, 2015; Pollatsek et al, 1992; Rayner et al, 1980; Schotter et al, 2012; Vasilev et al, 2019).…”
Section: Processing Of Upcoming Words During Readingmentioning
confidence: 99%
“…It is wellestablished that readers are able to process information about upcoming words in a sentence, that is, in the parafoveal field of vision, before their eyes move to fixate on them directly (reviews in Andrews & Veldre, 2019;Hyönä, 2011;Schotter et al, 2012;Vasilev & Angele, 2017). Eye movement studies have shown that skilled adult readers routinely process the orthography of upcoming words (Balota et al, 1985;Binder et al, 1999;Briihl & Inhoff, 1995;Inhoff, 1987Inhoff, , 1989aInhoff, , 1989bInhoff, , 1990Inhoff & Tousman, 1990;Johnson & Dunne, 2012;Johnson et al, 2007;Kirkby et al, 2022;McConkie & Zola, 1979;Milledge et al, 2021;Pagán et al, 2016;Rayner, 1975b;Rayner, McConkie, & Zola, 1980;Staroverova et al, 2023;Tiffin-Richards & Schroeder, 2015a;White et al, 2008;Williams et al, 2006), the phonology of upcoming words (Ashby & Rayner, 2004;Ashby et al, 2006;Chace et al, 2005;Henderson et al, 1995;Pan et al, 2016;Pollatsek et al, 1992Pollatsek et al, , 2000Tiffin-Richards & Schroeder, 2015a;Vasilev et al, 2019), as well as the semantics of words visible in the parafovea (for discussions see Hohenstein & Kliegl, 2014;Rayner et al, 1986Rayner et al, , 2014Sch...…”
mentioning
confidence: 99%
“…It has also been assumed that dyslexia may be due to an unusual masking of letters by flanking letters (crowding effect) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In this case, letters to the left and to the right of a letter decrease its recognition.…”
Section: What Are Causes Of Dyslexia?mentioning
confidence: 99%
“…Since the German ophthalmologist Oswald Berkhan [ 1 ] first described the symptoms of dyslexia in 1881 and Rudolf Berlin introduced the term ”dyslexia“ [ 2 ], numerous theories have been proposed about its causes and treatments, [ 3 , 4 ] (for review). The magnocellular theory of dyslexia [ 5 , 6 , 7 , 8 , 9 ], the theory of unusual foveal and parafoveal processing of letters including an unusual crowding effect [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], and the temporal summation theory [ 20 , 21 , 22 , 23 ] regard developmental dyslexia (DD) as a visual perceptual disorder. Other theories assume that DD results from an impaired ability to process auditory stimuli [ 24 , 25 , 26 , 27 ] or is caused by impaired control of reading eye movements [ 6 , 7 , 8 , 9 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%